Tekst i responsja w E. Suppl. 72-80 - Stępień, Piotr (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
In this article the author argues for the correctness of the text and the irregular responsion transmitted for E. Suppl. 72-80. He discusses two commonly accepted emendations for the antistrophe, which are then showed to be unsatisfactory for contextual reasons. Analysing the text of the strophe, he presents the special use of the noun prospolos in Greek drama; this allows him to reject Heath’s emendation for the strophe. Finally the author specifes three compositional characteristics of the lyrics of Euripides’ Suppliants which make the text and the irregular responsion in question highly probable in the form in which they are transmitted by the codex unicus L.
Text and responsion in E. Suppl. 72-80
Keywords: textual criticism; lyric metres; strophic structure